Skador på ytliga böjsenan hos ridhästar - Sjöström, Maria (2005)
Injuries of the superficial digital flexor tendon are common in racehorses with many reports on different treatment regimes. However there are few studies in riding horses. The purpose of this study was to document the result of conservative treatment of injuries on the superficial digital flexor tendon in riding horses and to find factors that may be important to the outcome.